Steel plate
A steel plate with controlled surface texture and composition, combined with optimized hot rolling conditions, addresses bending anisotropy issues, achieving high strength and bendability for automotive components.
Patent Information
- Application Number
- JP2023503734
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-02
- Filing Date
- 2022-02-22
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2042-02-22
AI Technical Summary
High-strength steel plates used in automobile components exhibit bending anisotropy, leading to cracks when bent perpendicular to the rolling direction, despite showing no cracks when bent parallel to it.
A steel plate composition with controlled surface layer texture and specific chemical elements, including C, Si, Mn, P, S, Al, Ti, and others, along with controlled hot rolling conditions to minimize shear band formation and reduce bending anisotropy.
The solution results in a steel plate with high tensile strength of 780 MPa or more, low bending anisotropy, and excellent bendability, suitable for automotive suspension parts.
Smart Images

Figure 0007617471000001 
Figure 0007617471000002 
Figure 0007617471000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a steel sheet. [Background technology]
[0002] Due to the growing need for weight reduction against the backdrop of energy issues, high-strength steel plates that allow for reduced plate thickness are increasingly being used in automobile and truck components. Many of these automobile body parts are formed by press working. In particular, suspension parts have complex shapes, so the high-strength steel plates used are required to have excellent bending workability.
[0003] For example, in Patent Document 1, the {100} <011> ~{223} <110> The average X-ray random intensity ratio of the orientation group is 3.0 or more, and {554} <225> , {111} <112> , and {111} <110> Patent Document 2 discloses a ferritic thin steel sheet in which the average value of the X-ray random intensity ratios of the above three crystal orientations is 3.5 or less, and further, at least one of the r-values in the rolling direction and the direction perpendicular to the rolling direction is 0.7 or less. Patent Document 2 discloses a cold-rolled steel sheet in which the (111) / / ND X-ray random intensity ratio is 3 or more, and the (100) / / ND X-ray random intensity ratio is 1 or less. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2001-303175 A [Patent Document 2] JP 2013-104114 A Summary of the Invention [Problem to be solved by the invention]
[0005] Incidentally, the present inventors conducted various bending tests on hot-rolled steel sheets having a tensile strength of 780 MPa or more, and found that, even if no cracks occurred when the bending ridge line was parallel to the rolling direction, cracks may occur when the bending ridge line was perpendicular to the rolling direction, i.e., parallel to the sheet width direction, and thus bending anisotropy exists.
[0006] An object of the present invention is to solve the above problems and to provide a steel sheet having high tensile strength, low bending anisotropy, and excellent bendability. [Means for solving the problem]
[0007] The present invention has been made to solve the above problems, and the gist of the present invention is the following steel sheet.
[0008] (1) Chemical composition, in mass%, C: 0.05-0.25%, Si: 0.2-2.0%, Mn: 1.2-3.0%, P:0.030% or less, S: 0.050% or less, Al: 0.01 to 0.55%, N: 0.0100% or less, Ti: 0.010 to 0.250%, The balance is Fe and impurities. The random intensity ratio of the texture in the surface layer of the steel sheet is 8.0 or less, the minimum angle between the maximum strength orientation of the {110} pole figure of the texture and the normal direction of the rolled surface of the steel sheet is 10° or less; steel plate.
[0009] (2) The chemical composition contains, in mass%, a part of the Fe replaced by Cr: 0.50% or less, Ni: 0.50% or less, and Cu: 0.50% or less, Contains one or more selected from The steel sheet according to (1) above.
[0010] (3) The chemical composition contains, in mass%, a part of the Fe replaced by Nb: 0.040% or less, V: 0.15% or less, Zr: 0.15% or less, Mo: 0.15% or less, and W: 0.15% or less, Contains one or more selected from The steel sheet according to (1) or (2) above.
[0011] (4) The chemical composition contains, in mass%, a part of the Fe replaced by Contains one or more selected from Sn, Sb and Te in a total amount of 0.100% or less; The steel sheet according to any one of (1) to (3) above.
[0012] (5) The chemical composition contains, in mass%, a part of the Fe replaced by Contains one or more selected from Ca, Mg and REM in a total amount of 0.0050% or less; The steel sheet according to any one of (1) to (4) above.
[0013] (6) The chemical composition contains, in mass%, a part of the Fe replaced by B: 0.0050% or less, Contains The steel sheet according to any one of (1) to (5) above. Effect of the Invention
[0014] According to the present invention, it is possible to obtain a steel sheet having a tensile strength of 780 MPa or more, low bending anisotropy, and excellent bendability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The present inventors have conducted studies and experiments on a method for reducing bending anisotropy of a high-strength steel plate having a tensile strength of 780 MPa or more, and have discovered the following.
[0016] When bending tests were performed, cracks occurred on the outer bend ridges. An investigation into the mechanism of crack initiation revealed that the occurrence of shear bands in the surface layer of the steel plate was a precursor phenomenon.
[0017] Therefore, the inventors further investigated methods for suppressing the occurrence of shear bands in the surface layer of a steel sheet, and as a result, discovered that controlling the texture in the surface layer of a steel sheet is extremely effective. That is, while attention has been focused only on the texture inside the steel sheet in the past, the inventors found that the texture in the surface layer of a steel sheet has a large effect on the occurrence of cracks in a bending test.
[0018] The present invention has been made based on the above findings. Each of the features of the present invention will be described in detail below.
[0019] (A) Chemical composition The reasons for limiting the content of each element are as follows. In the following description, "%" for the content means "mass %."
[0020] C: 0.05 to 0.25% C is an element necessary to ensure strength. If the C content is less than 0.05%, a tensile strength of 780 MPa or more cannot be obtained. On the other hand, if the C content exceeds 0.25%, the martensite becomes too hard, resulting in a deterioration in toughness and impairing weldability. Therefore, the C content is set to 0.05 to 0.25%. The C content is preferably 0.07% or more or 0.09% or more, and is preferably 0.22% or less, 0.20% or less, or 0.18% or less, and more preferably 0.15% or less.
[0021] Si: 0.2 to 2.0% Si is an element that contributes to improving strength. In addition, Si forms Fe2SiO4, which has a low melting point, on the surface of the steel sheet, and has the effect of reducing the bending anisotropy of the texture of the surface layer developed during hot rolling. On the other hand, if it is contained in excess, the problem of surface oxidation occurs during hot rolling. Therefore, the Si content is set to 0.2 to 2.0%. The Si content is preferably 0.3% or more or 0.5% or more, and is preferably 1.8% or less, 1.5% or less, or 1.3% or less.
[0022] Mn: 1.2-3.0% Mn has the effect of stabilizing austenite, facilitating the formation of a low-temperature transformation phase, and contributing to ensuring strength. On the other hand, if it is contained in excess, the volume fraction of ferrite decreases and elongation deteriorates. Therefore, the Mn content is set to 1.2 to 3.0%. The Mn content is preferably 1.5% or more or 1.7% or more, and is preferably 2.8% or less, 2.5% or less, or 2.2% or less.
[0023] P:0.030% or less P has the effect of increasing strength, so it may be actively added. However, if it is added in excess, embrittlement occurs due to grain boundary segregation, so if it is added, its content is set to 0.030% or less. The P content is preferably 0.025% or less, and more preferably 0.020% or less. There is no need to set a lower limit for the P content, and it may be 0%. However, since excessive reduction leads to an increase in manufacturing costs, the P content is preferably 0.001% or more. Note that, normally, P is mixed in at about 0.010% as an impurity level during the steelmaking stage.
[0024] S: 0.050% or less Since S forms sulfide-based inclusions and reduces elongation, its content is limited to 0.050% or less. If it is desired to ensure excellent elongation, the S content is preferably 0.0080% or less, and more preferably 0.0030% or less. There is no need to set a lower limit for the S content, and it may be 0%. However, since excessive reduction leads to an increase in manufacturing costs, the S content is preferably 0.0005% or more or 0.0010% or more.
[0025] Al: 0.01 to 0.55% Al is an element used for deoxidation. However, if it is contained excessively, it makes stable continuous casting difficult. Therefore, the Al content is set to 0.01 to 0.55%. Furthermore, if the Al content is high, austenite at high temperatures becomes unstable, and it becomes necessary to excessively increase the finish rolling temperature in hot rolling. Therefore, the content is preferably set to 0.50% or less, 0.45% or less, 0.40% or less, 0.30% or less, or 0.20% or less. In the present invention, the Al content means the content of acid-soluble Al (sol.Al). When retained austenite is generated to improve elongation, the total content of Al and the above-mentioned Si is preferably set to 1.0% or more.
[0026] N: 0.0100% or less Since N is an element that reduces elongation, its content is set to 0.0100% or less. The N content is preferably 0.0060% or less or 0.0040% or less. There is no need to set a lower limit for the N content, and it may be at the impurity level. Usually, about 0.0020% is mixed in at the steelmaking stage.
[0027] Ti: 0.010~0.250% Ti precipitates as carbides in the hot-rolled sheet structure, contributing to improving strength. Furthermore, it is an element that contributes to improving toughness by suppressing the coarsening of austenite grains. In particular, in the present invention, in order to control the texture of the surface layer as described later, finish rolling at high temperatures is essential. In order to suppress the coarsening of grains due to this, it is necessary to utilize the above effects. In addition, the strength of ferrite is improved, reducing the hardness difference with the hard second phase, and contributing to improving bendability. On the other hand, if it is contained excessively, coarse carbides or nitrides are formed during furnace heating before hot rolling, reducing elongation. Therefore, the Ti content is 0.010 to 0.250%. The Ti content is preferably 0.030% or more or 0.050% or more, and preferably 0.200% or less or 0.150% or less.
[0028] In addition to the above elements, the steel sheet of the present invention may further contain one or more elements selected from Cr, Ni, Cu, Nb, V, Zr, Mo, W, Sn, Sb, Te, Ca, Mg, REM, and B. There is no need to set a lower limit for the content of any of the elements, and the content may be 0%.
[0029] Cr:0.50% or less Ni: 0.50% or less Cu: 0.50% or less Cr, Ni and Cu have the effect of increasing hardenability and effectively forming martensite and / or bainite, and may be contained as necessary. However, if contained in excess, the formation of ferrite is suppressed, so the content of each of these elements is set to 0.50% or less. The content of each element is preferably 0.45% or less, 0.40% or less, or 0.35% or less. To obtain the above effects, it is preferable to contain one or more selected from the above elements in an amount of 0.10% or more, 0.15% or more, or 0.20% or more.
[0030] Nb: 0.040% or less Nb precipitates as carbides or nitrides, and has the effect of suppressing the recrystallization and coarsening of austenite and suppressing the deterioration of the toughness of the welded portion. Therefore, it may be contained as necessary. However, if contained excessively, it excessively increases the recrystallization temperature of austenite, making it difficult to control the texture in the surface layer, so the Nb content is set to 0.040% or less. The Nb content is preferably 0.035% or less or 0.030% or less. When it is desired to obtain the above effect, the Nb content is preferably 0.010% or more, 0.015% or more, or 0.020% or more.
[0031] V: 0.15% or less Zr: 0.15% or less Mo: 0.15% or less W: 0.15% or less V, Zr, Mo and W are elements that precipitate as carbides in the hot-rolled sheet structure and contribute to improving strength. In addition, they may be contained as necessary because they reduce the hardness difference with the hard second phase by improving the strength of ferrite and contribute to improving bendability. However, excessive inclusion of these elements not only inhibits elongation by forming coarse carbides, but also increases alloy costs. The contents of these elements are each set to 0.15% or less, preferably 0.12% or less. To obtain the above effects, it is preferable to contain at least one selected from the above elements at 0.01% or more, 0.03% or more, or 0.05% or more.
[0032] One or more selected from Sn, Sb and Te: 0.100% or less in total Sn, Sb and Te segregate on the surface of the steel, inhibit the formation of an internal oxide layer, particularly in high-Si steel, and contribute to improving pickling properties, so they may be included as necessary. However, if included in excess, they segregate at grain boundaries and reduce toughness, so their total content is set to 0.100% or less, preferably 0.050% or less. If the above effect is to be obtained, it is preferable to include them in a total content of 0.005% or more or 0.010% or more.
[0033] One or more selected from Ca, Mg and REM: 0.0050% or less in total Ca, Mg and REM (rare earth metals) may be added as necessary because they have the effect of refining oxides and nitrides precipitated during solidification and maintaining the soundness of the cast slab. However, since these elements are all expensive, their total content is set to 0.0050% or less, preferably 0.0030% or less. If the above effect is to be obtained, it is preferable to add them to a total content of 0.0005% or more or 0.0010% or more.
[0034] Here, REM refers to Sc, Y and 17 lanthanoid elements. The REM content means the total content of these elements. REM is added industrially in the form of misch metal.
[0035] B: 0.0050% or less B may be added as necessary because it contributes to improving the toughness of the steel plate by segregating at the grain boundaries and strengthening the steel plate. However, if it is added in excess, cracks will occur on the steel surface during casting, hindering productivity, so the upper limit is set to 0.0050% or less. The B content is preferably 0.0040% or less, and more preferably 0.0020% or less. When the above effects are to be obtained, it is preferable to add 0.0005% or more, 0.0007% or more, or 0.0010% or more.
[0036] In the chemical composition of the steel sheet of the present invention, the balance is Fe and impurities. Note that the term "impurities" refers to components that are mixed in due to various factors in raw materials such as ores and scraps and manufacturing processes during industrial production of steel, and are permissible within a range that does not adversely affect the present invention.
[0037] (B) Texture of the surface layer of the steel sheet Random intensity ratio: 8.0 or less Minimum angle between the maximum strength orientation of the {110} pole figure and the normal direction of the steel plate rolled surface: 10° or less As described above, by controlling the texture in the surface layer of the steel sheet, it is possible to suppress the formation of shear bands, which are a precursor phenomenon of cracks occurring on the outer bending ridge. Specifically, in the texture of the surface layer of the steel sheet, the random strength ratio is set to 8.0 or less, and the minimum angle between the maximum strength orientation of the {110} pole figure and the normal direction of the rolled surface of the steel sheet is set to 10° or less. In the present invention, the surface layer of the steel sheet means a region from the surface of the steel sheet to 200 μm in the depth direction.
[0038] The random intensity ratio of the texture in the surface layer of the steel sheet is preferably 7.0 or less, and more preferably 5.0 or less. The lower the random intensity ratio, the better, and there is no need to set a lower limit, but the effect saturates at 3.0 or less. The theoretical lower limit is 1.0. On the other hand, the minimum angle between the maximum strength orientation of the {110} pole figure and the normal direction to the rolled surface of the steel sheet is preferably 7.5° or less.
[0039] The random intensity ratio of the texture in the surface layer of the steel sheet and the minimum angle between the maximum intensity orientation of the {110} pole figure and the normal direction to the rolled surface of the steel sheet are measured using the following procedure: First, a cross section parallel to the rolling direction and thickness direction of the steel sheet is revealed, and the crystal orientation is measured at 0.5 μm intervals in an area 600 μm in the rolling direction and 200 μm from the surface in the thickness direction using the scanning electron beam backscatter diffraction (SEM-EBSD) method.
[0040] Next, from the obtained group of crystal orientations, the sample symmetry is set to a monoclinic system with the rolling direction-plate thickness direction cross section as the mirror plane, and the ODF is obtained using the spherical harmonic function expansion method with a half-value width of 5 degrees.The random intensity ratios of the crystal orientations are calculated at 5-degree intervals in Euler space, and the largest random intensity ratio is determined.
[0041] In addition, from the obtained crystal orientation group, the sample symmetry is set to a monoclinic system with the rolling direction-sheet thickness direction cross section as the mirror plane, and a {110} pole figure is calculated using the spherical harmonic expansion method with a half-value width of 5 degrees, and the angle between the maximum strength orientation and the normal direction to the rolling surface, i.e., the center point on the {110} pole figure, is determined.
[0042] Here, when analyzing the surface layer texture, it is extremely important to set the symmetry of the sample. In the analysis of the center of the thickness, the texture is generally analyzed with the sample symmetry set to the orthorhombic system. However, this analysis method does not allow accurate evaluation of the texture of the surface layer.
[0043] The results of the preliminary experiment conducted by the present inventors are described below. Test No. 24 in the examples described below is a comparative example manufactured by a method that deviates from the appropriate conditions. As a result of calculations performed on the steel sheet of Test No. 24 assuming the sample symmetry to be an orthorhombic system, the random intensity ratio was 3.7 and the angle between the center point on the {110} pole figure was 10°, which satisfied the provisions of the present invention. In contrast, as described above, when calculations were performed on the sample symmetry to be a monoclinic system, the random intensity ratio was 8.2 and the angle between the center point on the {110} pole figure was 10°, which deviated from the provisions of the present invention. This result also shows that the texture of the surface layer may not be evaluated correctly unless the method according to the present invention is used.
[0044] (C) Thickness There is no particular restriction on the thickness of the steel plate according to the present invention, but when used as a material for chassis parts of automobiles, trucks, and the like, the thickness of the steel plate is preferably 1.0 to 5.0 mm, and more preferably 1.2 to 3.2 mm.
[0045] (D) Metal structure at the center of plate thickness In the present invention, as described above, it is possible to improve the bendability by controlling the texture of the surface layer, and therefore there is no particular restriction on the metallographic structure in the center part of the sheet thickness of the steel sheet.
[0046] However, when it is desired to obtain good elongation while ensuring high strength, it is preferable that the metal structure in the center of the thickness of the steel plate contains, in terms of area ratio, 5 to 40% ferrite, a total of 60 to 95% martensite and bainite, and the remainder is less than 5%. Here, in the present invention, from the viewpoint of achieving both strength and elongation, it is preferable that the product of tensile strength and elongation at break is 10000 MPa% or more. It is more preferable that the product of tensile strength and elongation at break is 12000 MPa% or more, and further preferably 14000 MPa% or more.
[0047] Ferrite is soft and contributes to improving elongation. Therefore, in order to obtain excellent elongation while securing a tensile strength of 780 MPa or more, the area ratio of ferrite is preferably 5 to 40%. The area ratio of ferrite is more preferably 10% or more, more preferably 30% or less, and even more preferably 20% or less.
[0048] In addition, martensite and bainite improve the strength of the steel sheet, and by being appropriately mixed with ferrite, contribute to improving elongation. Therefore, the total area ratio of martensite and bainite is preferably 60 to 95%. Furthermore, in order to more reliably obtain the above effects, it is preferable that the area ratio of martensite is 15% or more or 20% or more. On the other hand, from the viewpoint of further securing toughness in addition to the above effects, it is preferable that the area ratio of martensite is 80% or less, and more preferably 70% or less or 60% or less. In the present invention, martensite includes not only fresh martensite but also tempered martensite.
[0049] The area ratio of the remainder other than ferrite, martensite, and bainite is preferably less than 5%. Specifically, pearlite, cementite, and retained austenite may be mixed as the remaining structure. From the viewpoint of ensuring uniform elongation, the total area ratio of pearlite and cementite is preferably less than 5%. In addition, although the retained austenite is a structure that improves uniform elongation, from the viewpoint of ensuring hole expandability, its area ratio is preferably less than 5%.
[0050] (E) Manufacturing method of steel plate An example of a method for producing a steel sheet according to the present invention will be described in detail below. The steel sheet according to the present invention can be obtained, for example, by a production method including the steps shown below.
[0051] <Slab manufacturing process> The steel billet to be subjected to hot rolling may be produced by a conventional method, i.e., a slab obtained by continuous casting or casting and blooming, or a steel plate obtained by strip casting, etc. may be used.
[0052] <Hot rolling process> The steel slab is then hot-rolled. In order to control the texture in the surface layer of the steel sheet, it is important to adjust the hot-rolling conditions. The conditions in the hot-rolling process are described in detail below.
[0053] Heating temperature: 1050~1300℃ In order to dissolve Ti in the steel, the heating temperature before hot rolling is set to 1050° C. or higher. On the other hand, in consideration of the durability of the heating furnace, the heating temperature is preferably set to 1300° C. or lower.
[0054] Effective rolling strain: 0.20~0.80 By adjusting the rolling ratio in the final reduction, or in the reduction before the final reduction, and setting the effective rolling strain defined below within the range of 0.20 to 0.80, it becomes possible to suppress the excessive development of the austenite texture and control the texture of the surface layer after γ-α transformation. The effective rolling strain will be explained below.
[0055] When the rolling stress in the reduction before the final reduction is F0 and the rolling stress in the final reduction is F1, if the value of (F1-F0) / F0 is less than 0.18, the rolling strain in the final reduction is taken as the effective rolling strain, and if the value of (F1-F0) / F0 is 0.18 or more, the sum of the rolling strains in the final reduction and the reduction before the final reduction is taken as the effective rolling strain.
[0056] Here, the rolling stress is the value obtained by dividing the rolling load by the product of the contact projection length Ld between the rolling roll and the steel sheet and the sheet width of the steel sheet. The contact projection length Ld is calculated by the following formula (1). The rolling strain is the absolute value of the true strain, that is, the effective rolling strain εeff is calculated by the following formula (2) or (3). Ld=√(Rd(hin-hout)) ···(i) Rd: Roll radius hin: entry plate thickness hout:Outside plate thickness When (F1-F0) / F0≧0.18 εeff=|ln(t0 / tini)+ln(t1 / t0)| ···(2) When (F1-F0) / F0<0.18 εeff = |ln(t1 / t0)| (3) tini: Plate thickness before the final reduction t0: Plate thickness after reduction before the final reduction t1: Plate thickness after final reduction
[0057] Finish rolling temperature: T SC ℃ or higher and 920℃ to 1080℃ The finish rolling temperature is T shown in the following formula (i). SC By setting the temperature at 920°C or higher, it is possible to control the texture in the surface layer of the steel sheet, and this is particularly effective in reducing the minimum angle between the maximum strength orientation of the {110} pole figure and the normal direction to the rolled surface of the steel sheet. The reason for this is not entirely clear, but SC It is considered that, at temperatures of 100° C. or higher and 920° C. or higher, Fe2SiO4 formed on the steel sheet surface softens, thereby reducing the amount of shear deformation imparted to the steel sheet surface. Here, the term "finish rolling temperature" refers to the temperature of the steel sheet after the final reduction. T SC =965+100×((5×P+0.5×Al) / Si) 2 -170×((5×P+0.5×Al) / Si) ···(i) In the formula, the element symbols represent the content (mass %) of each element.
[0058] On the other hand, if the finish rolling temperature exceeds 1080°C, there is a risk of deterioration of surface quality due to scale defects, so the finish rolling temperature in hot rolling is set to 1080°C or lower.
[0059] Time between final reduction and the reduction before the final reduction: 0.50 seconds or more If the time between the final reduction and the reduction just before the final reduction is less than 0.50 s, there is a high possibility that the temperature difference between the final reduction and the reduction just before the final reduction will be less than 15°C. In this case, the accumulated strain in the reduction just before the final reduction is likely to be carried over to the final reduction, the amount of shear deformation imparted to the steel sheet surface increases, and the minimum angle between the maximum strength orientation of the {110} pole figure and the normal direction of the steel sheet rolled surface increases. In addition, in some cases, this may lead to an increase in rolling stress in the final reduction, which may cause rolling trouble. Therefore, the time between the final reduction and the reduction just before the final reduction is set to 0.50 s or more so that the rolling entry temperature of the final reduction is 15°C or more lower than the rolling entry temperature of the reduction just before the final reduction. It is preferable that the time between the final reduction and the reduction just before the final reduction is set to 0.75 s or more. On the other hand, if it exceeds 3.0 s, the line speed will be significantly reduced and the finish rolling temperature will be set to T SC If the temperature is too high, the surface layer texture may not be controlled appropriately. Therefore, the time is preferably set to 3.0 s or less, and more preferably set to 2.0 s or less.
[0060] Time from finish rolling to start of water cooling: 0.50 seconds or more By setting the time from finish rolling to the start of water cooling to 0.50 s or more, the texture of the surface layer after γ-α transformation can be controlled, and this is particularly effective in reducing the random strength ratio. If the time from finish rolling to the start of water cooling is less than 0.50 s, the recrystallization of austenite is suppressed, and the texture of the austenite in the surface layer that has developed excessively due to rolling is inherited by the α phase after transformation, reducing the bendability. Therefore, the time from finish rolling to the start of water cooling is set to 0.50 s or more, preferably 0.80 s or more. On the other hand, if the time from finish rolling to the start of water cooling exceeds 3.0 s, the grain growth of austenite becomes significant, the amount of ferrite generated decreases, and there is a risk of impairing elongation. Therefore, the time from finish rolling to the start of water cooling is preferably set to 3.0 s or less, more preferably 1.5 s or less.
[0061] Primary cooling rate: 15℃ / s or more There is no particular restriction on the cooling rate after finish rolling. However, the primary cooling rate is preferably 15°C / s or more, more preferably 30°C / s or more. This makes it possible to suppress the precipitation of pearlite and the coarsening of precipitates, thereby improving strength. On the other hand, from the viewpoint of suppressing the excessive generation of martensite and securing ferrite, the primary cooling rate is preferably less than 60°C / s. The primary cooling rate means an average cooling rate obtained by dividing the difference between the finish rolling temperature and the higher of the primary cooling stop temperature described below or 500°C by the time required to cool to that temperature.
[0062] Primary cooling stop temperature: 600~680℃ After the finish rolling, the steel sheet may be cooled directly to the coiling temperature described later, but the cooling may be stopped in the range of 600 to 680°C in the middle in order to obtain ferrite in the metal structure inside the steel sheet. In order to obtain the effect more reliably, the primary cooling stop temperature is preferably 630°C or higher. In order to obtain this effect sufficiently, it is preferable to hold the steel sheet within the range of the primary cooling stop temperature for 2 to 15 s. By setting the holding time to 2 to 15 s, an appropriate amount of ferrite can be formed. The holding time is more preferably 5 to 10 s.
[0063] Secondary cooling rate: 10℃ / s or more When cooling is stopped at the above primary cooling temperature, secondary cooling is then performed. There is no particular restriction on the secondary cooling rate. However, the secondary cooling rate is preferably 10°C / s or more. This makes it possible to reduce the structure fraction of pearlite and retained austenite to less than 5%. On the other hand, from the viewpoint of suppressing flatness defects of the steel sheet and improving productivity, the secondary cooling rate is preferably 50°C / s or less. The secondary cooling rate means an average cooling rate obtained by dividing the difference between the primary cooling stop temperature and the coiling temperature by the time required to cool to that temperature.
[0064] <Winding process> Winding temperature: 100~500℃ There is no particular restriction on the coiling temperature, but from the viewpoint of generating bainite and / or martensite to ensure strength, coiling at a temperature of 500°C or less is preferable. On the other hand, if the coiling temperature is too low, flatness defects may occur in the steel sheet, which may hinder productivity. Therefore, the coiling temperature is preferably 100 to 500°C, and more preferably 150 to 450°C.
[0065] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. EXAMPLES
[0066] Steel having the chemical composition shown in Table 1 was melted in a vacuum melting furnace and reheated to 1050°C or higher, and then hot rolled in a small test hot rolling mill under the conditions shown in Table 2. After hot rolling, the steel was water-cooled to a temperature equivalent to that for coiling under the cooling conditions shown in Table 2 using a water-cooling device installed immediately after the rolling stand, and then placed in a heating furnace set to a temperature equivalent to that for the coiling described above, and held there for 30 minutes, after which it was slowly cooled to room temperature at 20°C / h to simulate the coiling process of an actual machine.
[0067] [Table 1]
[0068] [Table 2]
[0069] In Table 2, ST0 means the inlet temperature (°C) in the reduction just before the final reduction, ST1 means the inlet temperature (°C) in the final reduction, and FT means the finish rolling temperature (°C). Also, "interpass time" means the time between the final reduction and the reduction just before the final reduction, and "time from post-rolling to start of water cooling" means the time after finish rolling until the start of water cooling.
[0070] A cross section parallel to the rolling direction and thickness direction was cut out from the center of the thickness of the obtained steel plate, mirror-polished, and then etched with nital to reveal the metal structure, which was then observed using a SEM. Furthermore, a cross section parallel to the rolling direction and thickness direction of the steel plate was revealed, and the crystal orientation was measured at 0.5 μm intervals in a region 600 μm in the rolling direction and 200 μm from the surface in the thickness direction using SEM-EBSD.
[0071] From the obtained crystal orientation group, the ODF was calculated by the spherical harmonic function expansion method with the sample symmetry set to monoclinic and the half-width set to 5 degrees, the random intensity ratio of the crystal orientation was calculated at 5-degree intervals in Euler space, and the largest random intensity ratio was determined. Similarly, from the obtained crystal orientation group, the {110} pole figure was calculated by the spherical harmonic function expansion method with the sample symmetry set to monoclinic and the half-width set to 5 degrees, and the angle between the maximum intensity orientation and the center point on the {110} pole figure was determined.
[0072] Next, two JIS No. 5 tensile test pieces specified in JIS Z 2241:2011 were taken so that the direction perpendicular to the rolling direction of the steel plate coincided with the longitudinal direction of the test pieces, and the tensile strength TS and breaking elongation EL were measured in accordance with the same standard, and their average values were calculated.
[0073] Furthermore, the bending properties of the obtained steel sheets with TS of 780 MPa or more and TS × EL of 10,000 MPa% or more were evaluated by the following bending test. A rectangular test piece was cut out from each steel sheet, and after carefully removing burrs, it was used for the bending test. The test piece was 20 mm long along the bending ridgeline and 45 mm long in the direction perpendicular to the bending ridgeline, and was cut so that the bending ridgeline was parallel and perpendicular to the rolling direction.
[0074] Next, a V-shaped punch with a tip angle of 90° was prepared so that the ratio (Rp / t) of the plate thickness (t) of the above test piece to the punch tip radius (Rp) was 2.0 or 1.0, and the longitudinal center of the test piece was pressed against a die having a V-shaped groove with a groove angle of 90° installed on an Instron type universal testing machine with a force of 40 kN to perform a V-shaped bending test with an opening angle of 90°. The bending ridge after the V-bending test was observed with an SEM at a magnification of 40 times to confirm the presence or absence of cracks near the longitudinal center of the bending ridge. Then, the case where no cracks occurred on the bending ridge of the test piece was judged as ○, and the case where a crack occurred was judged as ×.
[0075] The results are shown in Table 3. In Table 3, the bendability when the bending ridge of the test piece is parallel to the rolling direction is called L-direction bendability, and the bendability when perpendicular is called C-direction bendability.
[0076] [Table 3]
[0077] As can be seen from Table 3, in Test No. 21, the finish rolling temperature (FT) was low and the effective rolling strain was too high. In Test No. 22, the time from finish rolling to the start of water cooling was short and the effective rolling strain was too high. In Test No. 23, the effective rolling strain was too high.
[0078] In test No. 24, the time after finish rolling to the start of water cooling was too short. In test No. 25, the finish rolling temperature (FT) was too low. In test No. 26, the time between the final reduction and the reduction before the final reduction was too long, which resulted in a low finish rolling temperature. In test No. 27, the time between the final reduction and the reduction before the final reduction was too short, which resulted in a small temperature difference on the entry side between the final reduction and the reduction before the final reduction. As a result, in these examples, the surface texture could not be controlled, resulting in poor bendability.
[0079] In test No. 28, the Mn content was low, and in test No. 29, the C content was low, so sufficient strength was not obtained. In test No. 30, the Ti content was not included, so the hardness difference between the ferrite and the hard second phase became large, and the bendability deteriorated. In test No. 31, the Mn content was excessive, so the elongation deteriorated. In test No. 32, the Nb content was excessive, so the surface texture could not be controlled, even though the manufacturing conditions were appropriate, and the bendability was poor.
[0080] In contrast, Test Nos. 1 to 20, which satisfied all of the requirements of the present invention, had high strength and excellent elongation, as well as excellent bendability, and no bending anisotropy was observed. [Industrial Applicability]
[0081] According to the present invention, it is possible to obtain a steel sheet having a tensile strength of 780 MPa or more, low bending anisotropy, and excellent bendability. Therefore, the steel sheet according to the present invention can be suitably used as a material for suspension parts of automobiles, trucks, etc.
Claims
1. The chemical composition, in mass%, is C: 0.05-0.25%, Si: 0.2-2.0%, Mn: 1.2-3.0%, P: 0.030% or less, S: 0.050% or less, Al: 0.01-0.55%, N: 0.0100% or less, Ti: 0.010-0.250%, Cr: 0 to 0.50%, Ni: 0 to 0.50%, Cu: 0 to 0.50%, Nb: 0 to 0.040%, V: 0 to 0.15%, Zr: 0 to 0.15%, Mo: 0 to 0.15%, W: 0-0.15%, One or more elements selected from Sn, Sb and Te, in total, 0 to 0.100%; one or more selected from Ca, Mg and REM, in total 0 to 0.0050%; B: 0 to 0.0050%, The balance is Fe and impurities. The random intensity ratio of the texture in the surface layer portion of the steel sheet is 8.0 or less, the minimum angle between the maximum strength orientation of the {110} pole figure of the texture and the normal direction of the rolled surface of the steel sheet is 10° or less; A cross section parallel to the rolling direction and the thickness direction of the steel sheet was revealed, and the crystal orientation was measured at 0.5 μm intervals in a region 600 μm in the rolling direction and 200 μm from the surface in the thickness direction by electron backscatter diffraction method. From the obtained group of crystal orientations, the sample symmetry is set to a monoclinic system with the cross section as a mirror plane, and an ODF is obtained by a spherical harmonic function expansion method with a half-value width of 5 degrees. Random intensity ratios of the crystal orientations are calculated at 5 degree intervals in Euler space, and the largest random intensity ratio among them is determined as the random intensity ratio of the texture. From the obtained group of crystal orientations, the sample symmetry is set to a monoclinic system with the cross section as a mirror plane, and a {110} pole figure is calculated by a spherical harmonic expansion method with a half-value width of 5 degrees, and the angle between the maximum strength orientation and the normal direction of the rolled surface, i.e., the center point on the {110} pole figure, is set as the minimum angle between the maximum strength orientation of the {110} pole figure of the texture and the normal direction of the rolled surface of the steel sheet. steel plate.
2. The chemical composition is, in mass %, replacing a part of the Fe, Cr: 0.10-0.50%, Ni: 0.10 to 0.50%, and Cu: 0.10-0.50%, Contains one or more selected from The steel sheet according to claim 1.
3. The chemical composition is, in mass %, replacing a part of the Fe, Nb: 0.010-0.040%, V: 0.01-0.15%, Zr: 0.01 to 0.15%, Mo: 0.01 to 0.15%, and W: 0.01-0.15%, Contains one or more selected from The steel sheet according to claim 1 or 2.
4. The chemical composition is, in mass %, replacing a part of the Fe, Contains one or more selected from Sn, Sb and Te in a total amount of 0.005 to 0.100%; The steel sheet according to any one of claims 1 to 3.
5. The chemical composition is, in mass %, replacing a part of the Fe, Contains one or more selected from Ca, Mg and REM in a total amount of 0.0005 to 0.0050%; The steel sheet according to any one of claims 1 to 4.
6. The chemical composition is, in mass %, replacing a part of the Fe, B: 0.0005-0.0050%, Contains The steel sheet according to any one of claims 1 to 5.
Citation Information
Patent Citations
Ferritic thin steel sheet excellent in shape freezability and its producing method
JP2001303175A
Cold rolled steel sheet having excellent bending workability and method for producing the same
JP2013104114A
Hot rolled steel sheet
JP2016050335A
High strength hot rolled steel sheet excellent in hole expandability and weld zone fatigue property and manufacturing method therefor
JP2017206764A
High-strength cold-rolled steel sheet with excellent local formability, and manufacturing method therefor
WO2012141265A1